Seventh-graders 'experiences and wishes about mathematics teaching in Finland - Pehkonen, Erkki (NOMAD Nordic Studies in Mathematics Education, 1994)
The experiences and wishes of about fivehundred Finnish seventh-graders towards mathematics teaching are surveyed using a postal questionnaire. The pupils' responses to three open-ended questions in the questionnaire are classified into six categories: Teacher/teaching, Mathematical topics, Learning control, Pupil, Interaction and working forms, and Resources. Most of the responses (65 - 70 %) are in the first two categories. In addition, a significant percentage (more than 10 %) of the responses are in the class "Pupil" for experiences and in "Interaction and working forms" for wishes. Differences in responses given by boys and girls are discussed and some general suggestions for change in mathematics instruction, based on pupils' experiences and wishes, are put forward.